Aspergillosis in free-ranging Magellanic penguins. (10th February 2023) - Melo, Aryse Martins; Poester, Vanice Rodrigues; Trápaga, Mariana Rodrigues; Stevens, David A; Canabarro, Paula Lima; Adornes, Andréa Corrado; da Silva, Andrine Paiva; Estima, Sérgio Curi; Frere, Esteban; Sabino, Raquel; Xavier, Melissa Orzechowski
Abstract: We evaluated the mortality due to aspergillosis in free-ranging Magellanic penguins during their migration and the reproductive season. A total of 98 carcasses of penguins were collected along 370 km of coastline in Southern Brazil, between June 2017 and October 2019, and from reproductive colonies in Patagonian Argentina, in January 2019. All animals were necropsied, and only proven cases were computed. Aspergillosis was diagnosed in 2.5% of the penguins evaluated during their migration route. Our study, of the Southern coast of Brazil, is the first to demonstrate that aspergillosis is an important cause of mortality in free-ranging penguins. The implications of these findings in the One Health context are discussed. Lay Summary: We evaluated the mortality due to aspergillosis in free-ranging Magellanic penguins during their migration and the reproductive season. The mortality rate of penguins was 2.5% during their migration route. Our study is the first to demonstrate aspergillosis as an important cause of mortality in free-ranging penguins.